Robotics : 12th Latin American Robotics Symposium and Third Brazilian Symposium on Robotics, LARS 2015/SBR 2015, Uberlândia, Brazil, October 28 - November 1, 2015, Revised selected papers /: 12th Latin American Robotics Symposium and Third Brazilian Symposium on Robotics, LARS 2015/SBR 2015, Uberlândia, Brazil, October 28 - November 1, 2015, Revised selected papers. (2016) - Unknown
No abstract available